The Phenomenon of Bang-Abang (Bank Titil) According to a Review of Fiqh Muamalah - Ulya Dharojah; Khodimul Wahid; Kholid Kholid (Universitas Islam Negeri Sumatera Utara, 2025)
This study examines the phenomenon of bang-abang, which is the term used by the people of Bangkalan to refer to loan sharks in the Kasorjan market in Bangkalan District, Bangkalan Regency, which is a market located in the densely populated center of Bangkalan. The market is a place where sellers and buyers meet to conduct transactions. As time goes by, the market has become more than just a place where sellers and buyers meet to conduct transactions. The large number of people who gather at the market is also used to offer financial services, one of which is titil banks that offer loan services. This study uses a qualitative Islamic phenomenological method, conducting observations and interviews, as well as analyzing the conformity of transactions carried out by bang-abang with the teachings of Islamic muamalah fiqh. The results of this study indicate that the loan transactions conducted by the bang-abang are not in accordance with Islamic law because they involve interest, which is clearly prohibited. This may occur due to a lack of understanding and awareness among the community regarding transactions that comply with Islamic law, as well as unstable economic conditions and urgent community needs